The Joint Ministerial Decree (SKB) of Islamic Defenders Front (FPI): Quo Vadis The Rule of Law and Human Rights? - Fradhana Putra Disantara (Musamus Law Review, 2021)
The freedom of association is one of the fundamental rights of a country. However, in Indonesia, the problems regarding of the legitimacy and recognition of the right to freedom of association have become stronger after the issuance of a The Joint Ministerial Decree (SKB) regarding the dissolution of the Islamic Defenders Front (FPI). This research is a legal research. This research uses statutory and conceptual approaches by using primary and secondary legal materials. The two legal materials are inventoried in order to obtain a prescriptive legal analysis; as well as providing a holistic conceptual study of the legal issues discussed. The research result states that the dissolution of FPI by the government is an act that violates human rights, particularly the right to freedom of association. The government uses the doctrine of the militant democracy to dissolve FPI. Then, the dissolution of FPI by SKB contradicts by the principle of the rule of law. Therefore, the dissolution of FPI was not carried out through to the court. Therefore, it is necessary to follow up on the action against 'radical mass organizations' in the form of presidential regulations or government regulations as a derivative renewal of the regulations concerning mass organizations.